2010
DOI: 10.1097/sla.0b013e3181fc3c73
|View full text |Cite
|
Sign up to set email alerts
|

Infrapopliteal Percutaneous Transluminal Angioplasty Versus Bypass Surgery as First-Line Strategies in Critical Leg Ischemia

Abstract: When feasible, infrapopliteal PTA as a first-line strategy is expected to achieve similar long-term results to bypass surgery in CLI when redo surgery is actively utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…As percutaneous transluminal angioplasty (PTA) is increasingly used as an alternative primary therapy for critical limb ischemia 47 , a growing body of literature has accumulated comparing PTA to bypass. To date, there has only been one large randomized control trial comparing PTA to bypass for CLI 3 , which suggested that bypass should be offered first over balloon angioplasty in patients with available venous conduit who are expected to live longer than 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As percutaneous transluminal angioplasty (PTA) is increasingly used as an alternative primary therapy for critical limb ischemia 47 , a growing body of literature has accumulated comparing PTA to bypass. To date, there has only been one large randomized control trial comparing PTA to bypass for CLI 3 , which suggested that bypass should be offered first over balloon angioplasty in patients with available venous conduit who are expected to live longer than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Citing lower perioperative morbidity and mortality, high technical success, and equivalent rates of limb salvage, some groups now endorse PTA as a comparable, if not preferred first-line therapy for patients with critical limb ischemia (CLI) 48 . Guidelines for PTA of the infrapopliteal vessels are less well defined than those for the iliac or femoropopliteal segments and in fact, the original TransAtlantic Inter-Society Consensus (TASC) I classification of infrapopliteal lesions 9 are notably absent from the TASC II guidelines, which offer no specific recommendations on the management of these lesions 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[84][85][86] Although higher complexity tibial disease has been traditionally treated surgically, Schmidt et al 87 reported 95.6% limb salvage at 12 months for complicated (average length 184 mm with 64.9% occlusions) infrapopliteal disease. A recent meta-analysis showed that even with severe tibial disease and poor distal run-off, reasonable rates of limb salvage can be achieved with angioplasty alone.…”
Section: Infrapopliteal Balloon Angioplasty For CLImentioning
confidence: 99%
“…Peripheral percutaneous transluminal angioplasty is a method for treating CLI, especially infrapopliteal level, with outcomes similar to those of bypass surgery 4,5. Ultimate aim of revascularization in patients with CLI is to prevent limb loss, including major amputation to improve patient's quality of life, and to prolong survival.…”
Section: Discussionmentioning
confidence: 99%